Bioreduction of precious and heavy metals by Candida species under oxidative stress conditions. Issue 6 (7th January 2019) - Moreno, Abel; Demitri, Nicola; Ruiz‐Baca, Estela; Vega‐González, Arturo; Polentarutti, Maurizio; Cuéllar‐Cruz, Mayra
Summary: The aim of the present work was to evaluate whether Candida species can reduce both precious and toxic pure metals from the respective molecular ions. From these results, the nanoparticles formed were studied using scanning electron microscopy with energy‐dispersive spectroscopy, Raman spectroscopy, X‐ray fluorescence spectroscopy and synchrotron radiation. Our results showed that the metal ions were reduced to their corresponding metallic nanoconglomerate or nanoparticles by Candida species. This is the first report on how yeasts of this genus are capable of achieving homeostasis (resilience) in the presence of metal ions of both precious and toxic metals by reducing them to a metallic state. Abstract : Proposed mechanism through which Candida species synthesize NPs of gold, silver and lead, as well as mercury drops.